Detección de bacterias de importancia clínica en el agua del río Guamote, 2019 - Indira Kasandra, Tipán Pillajo (2019)
The present investigation focused on determining bacteria of clinical interest in the waters of the Guamote River, showing pathogens causing infections that could involve the therapeutic failure. The contamination the water resource is the problem that worldwide has become the most significant emphasis, due to the enormous proliferation of pathogenic bacteria for man, which have acquired antimicrobial resistance causing antibiotic inefficiency for various types of diseases and infections. A study was conducted with a qualitative approach and descriptive research type, with a non-experimental field design, and a transversal cohort, which occurred with the collection of water samples at six different geographical points, to proceed with the measurement of pH, the temperature of the environment and water. Bacterial identification was performed using the Gram technique by obtaining pure strains in the Blood, CLED, MacConkey agars, with their respective interpretation of biochemical tests to classify the bacteria previously affected by gender and species, measured by the Kirby Bauermethod the bacterial susceptibility and thus identifying the presence of 8 types of bacteria of clinical interest: Aeromonas spp., Enterococcus spp., and various types of Enterobacteria (Klebsiella pneumoniae, Klebsiella oxytoca, Citrobacter amalonaticus, Proteus mirabilis, Proteus vulgaris, Citrobacter diversus). Determining most bacterias demonstrate resistance to antibiotics such as second and third-generation cephalosporins, quinolones, and aminoglycosides, concluding that the Guamote River shows massive contamination of pathogenic bacteria resistant to antibiotics for clinical use.